Kepribadian dan Profesionalitas Guru Dalam Meningkatkan Proses Belajar Mengajar Siswa - Melly Nuryani (Jurnal Dirosah Islamiyah, 2019)
The teacher is a professional in the field of teaching and education, referring to the National Education Law No. 20of 2003 concerning the National Education System Article 1 Item 14. Effective action as a professional in the teaching field must have knowledge and expertise, commitment and motivation as learning objectives. Knowledge and expertise in a teacher has an impact on personality in carrying out professionalism in addition to following technological developments appropriately in responding to current developments and from time to time. Internet technology in this case has helped a lot in improving the quality of developing a teacher to adjust to the development of the technology. From the explanation it is necessary to examine the personality and professionalism of teachers in the teaching and learning process of students by focusing MTSN 02 Bogor research. The formation of a learning environment that ASRI (Safe, Healthy, Clean and Beautiful) can create an atmosphere of active student learning about self-potential, personality, intelligence, character and skills for the progress of the nation and state. Besides that there are KKG (Teacher Working Groups) in the form of FDG (Teacher Discussion Forum) in an effort to share knowledge with other school teachers, Promissory (Semester Program), Prota (Annual Program) and PTK (Class Level Research) conducted internally in each school. The need for quality of teaching, intensity in learning both a teacher and in order to improve professionalism is very important for that the formulation given is in the form of research on teacher professionalism, teacher personality and student teaching and learning process based on the results achieved in graduates and students who will take the final exam of learning at MTsN 02 Bogor. Sources of data are taken through regular questions to the principal, vice principal in the field of curriculum, teachers who teach at the school. The procedure taken in data collection is by interview, observation and documentation.The data generated in the form of interviews, data on student achievement in the competition, the results of graduates from 2013 to 2018 and the results of the graduates were accepted at the school desired by students as a form of secondary school that can accommodate them. In general the objectives of the learning and learning process by using refer to professionalism as personality maturity is very useful in developing the quality of student education.